Analysis of sprites from video observations made by the Croatian Meteor Network (Rudarsko-geološko-naftni zbornik, 2020)
Sprites are optical phenomena belonging to the category of transient luminous events. They were observed using cam- eras of the Croatian Meteor Network. The sprite images extracted from the recordings from cameras located in Rijeka and Višnjan were analysed using two methods. Sprites recorded on the night of 2017/05/31 at 21:46:18.781 and 22:03:27.299 only from the camera in Rijeka were analysed using the single-station analysis method. This method works on the as- sumption that sprites occur directly above the parent lightning and uses the lightning strike location provided by the Blitzortung website together with camera recordings from one station to make the spatial positioning of the sprite pos- sible. Sprites recorded on the night of 2017/05/31 at 21:57:44.376 and 22:07:16.440 from both cameras in Rijeka and Višnjan were analysed using the double-station analysis method, which is based on the lines of sight method. Both double-station sprites were also analysed using the single-station analysis method. The resulting heights and lateral distances were compared. It was concluded that this method of single-station analysis may provide a good estimate of the sprite location in case of small lateral distances between the sprite and parent lightning, while in other cases, errors may be significant. The double-station analysis method is preferred whenever possible, as it is mathematically exact and the errors arising from it depend only on the quality of the observation data.